Measured ocean acidification parameters (SST, SSS, pHt, DO%, DIC, AT) throughout the surface seawater in the Equatorial Pacific, Gorgona Island (november 2020 and june 2021) - Simón Gutiérrez Duque (PANGAEA, 2025)
This dataset contains discrete measured and calculated surface seawater properties from samples taken on the first week of every month over the course of one or two days between 11/2021 and 07/2022 (9 months) at the Equatorial Pacific region off the coast of Colombia, around Gorgona island National Natural Park. The dataset contains also measured monthly sea-surface temperature (SST), sea-surface salinity (SSS), pH in total scale (derived directly from in situ pH measurements) with depth of 1.8 metres along 7 sampling sites in a coast-ocean gradient (1 to 7) with the following geographical coverage: 1. Lat. -78.201138 Lon. 3.0163611; 2. Lat. -78.221416 Lon. 2.9705833; 3. Lat. -78.163861 Lon. 2.9960278; 4. Lat. -78.101555 Lon. 2.9473889; 5. Lat. -78.101555 Lon. 2.9322222; 6. Lat. -78.122865 Lon. 2.8756667; 7. Lat. -77.979865 Lon. 2.7204915. The measurements were taken with two CTD divers (SonTek CastAway-CTD and Eijkelkamp CTD-Diver 11.11.60) and one Niskin bottle (5L). The water samples where taken to a oceanography lab in the Pontifical Xavierian University to be tested for total alkalinity (TA), and to the Autonomous University of Baja California for Dissolved Inorganic Carbon (DIC) measurements. This was done in order to calculate the carbon fluxes on a monthly scale throughout nine months during the 2021-2022 La Niña year for the whole study site, allowing for observations in the spatiotemportal flux behavior variability (shown in dataset as fco2_measured).